Perforated Tube vs. Soxhlet Apparatus: A New Extraction Tool Confirming by Clove Sample and GC-Mass Analysis - Kafa Khalaf (Iraqi Journal of Industrial Research)
In this paper, a new efficient extraction tool of bioactives from plant parts was designed, applied, and compared with Soxhlet apparatus. This tool was a Quickfit®- Pyrex® glass tube perforated easily inserted in round flask containing solvent. Clove buds in both non-grinded and grinded form were analyzed by GC-Mass. Our observations were gotten from designing and using perforated tube compared to Soxhlet apparatus for Clove buds’ extraction. It is a simplest tool in designing and handling than Soxhlet apparatus that ensured more contact between Clove buds in their bag and used solvent than Soxhlet. Employing bag sewed from face mask is low cost than high quality Soxhlet - cellulose thimble. Furthermore, this sewed bag can be discharged from its content, cleaned, and reused but expensive cellulose thimble is made for one use. Perforated tube presents a good choice for efficient-short extraction time, minimum sample weight and solvent volume resulting higher quantity of Clove bioactives compared to Soxhlet. By analytical foundations, using grinded Clove gave different qualitative-quantitative analysis of the tested bioactives in the extracted solution compared to non- grinded buds. Eugenol was the major constituent in non- grinded buds while grinded powder gave 2-methoxy-3-(2-propenyl)-phenol as a maximal bioactive. This new tool may be used with less solvent quantity for better continuous extraction series however Soxhlet must be used with more than half flask volume to get fast-efficient extraction. Also, Soxhlet needs direct heating source however perforated tube may be applied in both direct heating and water bath. These notes are important in using low boiling solvent (volatile) for better extraction. Because extraction is not limited to plant parts, this new tool may be used as a general extraction tool. So to guarantee getting higher quantities of volatile constituents with easier steps, perforated tube is an excellent choice.